PRONUNCIATION MATERIALS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Pronunciation is increasingly popular in professional conferences where sessions are often filled to overflowing. Similarly, pronunciation materials today show up in a wide variety of sources. Baker and Murphy (2011) tell us that “the past decade has witnessed an explosion in the number of … classroom textbooks; teacher’s manuals; classroombased research reports; teacher-training books; book chapters; journal articles; CDROMs; videos, computer software; Internet resources, most of  which are geared directly toward ESL/EFL teachers” (p. 37). This explosion means that research into pronuncation materials needs to be based on sound research and best practices. Grant (1995) provided an early look at pronunciation materials development, but little attention has been paid to this area until recently. This chapter presents principles that should underlie pronunciation materials and then examines how four skills books follow those principles.